Model Pendidikan Agama Islam Berbasis Keluarga: Analisis Pola Asuh Keagamaan dalam Keluarga Kontemporer - Meu’ Auliahaq Ifftida’Aini; Triono Ali Mustofa (Al-Mudarris, 2026)
This study examines Islamic religious education within Muslim families in the digital era, focusing on adaptive Islamic parenting in shaping children’s spiritual character. Grounded in the concepts of fitrah, adab, and uswatun hasanah, the study explores how family education responds to digital media exposure and changing parent–child interaction patterns.A qualitative case study approach was employed with two Muslim families as embedded case units. The selection of two families is justified by the depth-oriented nature of case study research, which prioritizes intensive, contextual understanding rather than statistical generalization. The two families were purposively selected based on specific criteria: (1) Muslim nuclear families with children aged 7–15 years, (2) regular exposure to digital devices in daily life, (3) willingness of both parents to participate in interviews and observation, and (4) contrasting parenting styles in religious education practices. Data were collected through in-depth interviews and participant observation, and analyzed using the Miles and Huberman interactive model involving data reduction, display, and conclusion drawing. The findings show that parenting combining democratic discipline, religious habituation, and consistent role modeling strengthens children’s internalization of Islamic values. In contrast, permissive parenting with weak religious exemplification results in inconsistent religious behavior. Theoretically, the study extends fitrah by showing that children’s innate spirituality requires structured parental mediation in the digital environment. Adab is expanded to include digital ethics in media use, while uswatun hasanah is reconceptualized as continuous and visible moral modeling in both offline and online contexts. The study thus contributes a contextual model of Islamic parenting that operationalizes these concepts in the digital age.